Pengaruh Net Profit Margin, Return on Asset, Return on Equity dan Inflasi terhadap Harga Saham - Fikri Zamzami; Nanu Hasanuh (Owner : Riset dan Jurnal Akuntansi, 2021)
The researcher conducted this research because he was interested in investing in uncertain returns, because this was because the researcher used the variables in this study as consideration.This study aims to determine the effect of Net Profit Margin (NPM), Return On Asset (ROA), Return on Equity (ROE), and Inflation on Stock Prices in LQ45 companies listed on The Indonesia Stock Exchange (IDX) for the period 2015-2019. Stock prices can be an assessment of investor to buy shares of the company. Stock prices tend to fluctuate, so it needs proper observation when making stock purchases. Independent variables in this study are Net Profit Margin (NPM), Return on Asset (ROA), Return on Equity (ROE), and Inflation. Dependent variable in this study is Stock Prices. This study uses quantitative methods using descriptive analysis and verification analysis of companies listed in LQ45. Data analysis technique using the classic assumption test, multiple linear regression, and hypothesis testing using SPSS 21 application. Based on the result of this study indicate the partially Net Profit Margin (NPM) has no effect on Stock Prices. Return on Asset (ROA) has no effect on Stock Prices. Return on Equity (ROE) has a significant effect on Stock Prices. Inflation has no effect on Stock Prices. Simultaneously Net Profit Margin (NPM), Return On Asset (ROA), Return on Equity (ROE), and Inflation have a significant effect on Stock Prices.